BIODIESEL SYNTHESIS THROUGH NYAMPLUNG OIL ESTERIFICATION AND TRANSESTERIFICATION USING ULTRASONIC WAVES ASSIST - Haryono Haryono; E. Evy Ernawati; Rukiah Rukiah; Susi Suryani (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2017)
This study was aimed at synthesizing biodiesel of nyamplung oil through esterification and transesterification process using ozonation and ultrasonic waves assist. The ozonation was done for 30 minutes, while the transesterification reaction was aided by ultrasonic wave frequency variation 28 and 35 kHz for 30 minutes. The results show that the use of ultrasonic waves in frequency of 35 kHz in the transesterification reaction to the ozonized nyamplung oil from esterification reaction produced biodiesel on the standards of Indonesian biodiesel. The biodiesel product in this study has 0.70 mgKOH/g biodiesel acid value, iodine number 50.34 g I2/100 g, the flash point of 122.4°C, cetana numbers of 102.5, density of 0.9088 g/cm3, and a viscosity of 9.5 cSt